Physical activity, sleep quality and life satisfaction in adolescents: A cross-sectional survey study - Cao, Yunhua; Yang, Zhen; Yu, Yongbo; Huang, Xin (Frontiers in Public Health, 2022)
Background Physical activity, sleep is an important component of adolescents' 24-h movement behavior, and life satisfaction predicts adolescent physical and mental health. However, few studies have explored the relationship between the two variables among Chinese high school students. Consequently, this study aimed to explore the relationship between sleep quality and life satisfaction among Chinese high school students. Methods This cross-sectional study was conducted in October 2020 in five high schools in Xuchang City, China. High school students from senior 1 to senior 3 were asked to fill up a questionnaire of demographic characteristics and validated screen instructions for sleep quality (Pittsburgh Sleep Quality Index) and life satisfaction (Satisfaction with Life Scale). The multivariate regression model was applied to explore the association between sleep quality and life satisfaction. Results A total of 1127 individuals (51.1% males) participated in this survey, and the prevalence of poor sleep quality was 42.3%. The mean score on the Satisfaction with Life Scale was 16.72 ± 5.67, according to the corresponding scoring criteria, with 15–19 being generally dissatisfied. After controlling for demographic variables, the contribution of subjective sleep quality (β = – 0.181, p < 0.01), sleep duration (β = – 0.080, p < 0.01) and daytime dysfunction (β = – 0.311, p < 0.01) to life satisfaction of high school students increased to 23.2%, indicating that subjective sleep quality, sleep duration, and daytime dysfunction were 22.9% predictive of life satisfaction among high school students. And also, physical activity on schooldays and weekend days were associated with better sleep quality and higher life satisfaction (p < 0.05). Conclusions Among Chinese high school students, the prevalence of sleep problems was high, and the majority of students held moderate life satisfaction. Sleep quality was positively correlated with life satisfaction among Chinese high school students, with better sleep quality resulting in higher life satisfaction among students.